2021
DOI: 10.1007/s11926-021-01002-0
|View full text |Cite
|
Sign up to set email alerts
|

ANCA Status or Clinical Phenotype — What Counts More?

Abstract: Purpose of Review There is ongoing debate concerning the classification of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis. That is, whether classification should be based on the serotype (proteinase 3 (PR3)- or myeloperoxidase (MPO)-ANCA) or on the clinical phenotype (granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA)). To add clarity, this review focused on integration of the most recent literature. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 88 publications
1
9
1
1
Order By: Relevance
“…This may reflect the more chronic, smoldering course of MPO-ANCA disease, compared to the acute but relapsing nature of PR3-ANCA. 14 , 31 , 32 This finding is further supported by a study done by Basu et al., 33 where, in the supplementary data, it was shown that patients who are MPO-ANCA positive, were more likely to have higher rates of fatigue than MPO-ANCA negative patients (p = 0.05). In contrast, patients who were currently PR3-ANCA positive did not have higher rates of fatigue than PR3-ANCA negative patients did (p = 0.47).…”
Section: Discussionsupporting
confidence: 63%
“…This may reflect the more chronic, smoldering course of MPO-ANCA disease, compared to the acute but relapsing nature of PR3-ANCA. 14 , 31 , 32 This finding is further supported by a study done by Basu et al., 33 where, in the supplementary data, it was shown that patients who are MPO-ANCA positive, were more likely to have higher rates of fatigue than MPO-ANCA negative patients (p = 0.05). In contrast, patients who were currently PR3-ANCA positive did not have higher rates of fatigue than PR3-ANCA negative patients did (p = 0.47).…”
Section: Discussionsupporting
confidence: 63%
“…This might reflect differences in pathogenesis between both entities. Several independent investigations have found a higher relapse rate among individuals with PR3- as compared with MPO-ANCA vasculitis 1. Serum PR3-ANCA positivity and increasing titres of PR3-ANCA during follow-up were each associated with relapse in several studies 5 35.…”
Section: Discussionmentioning
confidence: 97%
“…Serum PR3-ANCA positivity and increasing titres of PR3-ANCA during follow-up were each associated with relapse in several studies 5 35. Notably, only few patients with MPO-ANCA vasculitis relapsed during the follow-up of the RAVE trial, and MPO-ANCA vasculitis usually presents at older age and with impaired kidney function, which may have been negative predictors of relapses 1. Findings concerning baseline sICPs as predictors for relapse under RTX treatment in MPO-ANCA vasculitis were limited by the lower numbers, but in part followed the trend shown in the substantially larger PR3 ANCA vasculitis cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread adoption of the 1994 Chapel Hill Consensus definitions for vasculitis resulted in the recognition of MPA as an entity distinct from polyarteritis nodosa 6 . With the acknowledged imperfections of the ACR and Chapel Hill Consensus criteria for classification, there has been debate as to whether it is preferable to classify patients by ANCA serotype (proteinase 3 and myeloperoxidase (MPO)) alone rather than by the clinical phenotype 108 . It is hoped that the new EULAR–ACR classification system, which incorporates ANCA status, will help to resolve this debate 8 – 10 .…”
Section: Small Vessel Vasculitismentioning
confidence: 99%